A new Setacheres (Copepoda, Siphonostomatoida, Asterocheridae) associated with Ircinia felix (Duchassaing & Michelotti) (Porifera) from Brazil - Borges, Camila C.; Neves, Elizabeth G.; Johnsson, Rodrigo (Zootaxa, 2017)
Recent surveys of the copepod fauna associated with the sponge Ircinia felix (Porifera, Dictyoceratida) in Brazil resulted in the discovery of a new siphonostomatoid species belonging to a recently erected genus of Asterocheridae. Setacheres portobarrensis sp. nov. possesses a 21-segmented antennule, with 3 free distal segments, after the aesthetasc. The third exopodal segment of leg 3 shows a distal seta instead of a spine as in some other congeners. The new species shows several unique features on the third endopodal segment of the antenna, the mandibular stylet, the inner lobe of the maxillule, and setules and spinules located in specific regions of legs 1 to 4. Setacheres portobarrensis sp. nov. follows the same distributional pattern as its congeners, and this is the first record of a siphonostomatoid copepod associated with Ircinia felix.